Natural Resources and Socio-Economic Progress - L. M. Kapitsa (Vestnik MGIMO-Universiteta)
The article reviews international debates on development problems of the resource-based economies. It draws atten tion to causes and mechanisms of the so-called "resource curse" and symptoms of systemic breakdowns and stagnant phenomena in resource-based economies named "Dutch disease". Specific attention is given to the role of national elites and institutions in the emergence of "Dutch disease", preservation of economic backwardness and/or de-industrialization of resource-rich countries. The author also considers new approaches to resolving the problem of'resource-curse", in particular, return to traditional instruments of economic diversification as industrialization and protectionism.